English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

How to use the Product Rule for:

f(x) = (cos x) e^-xsqrt3

2007-01-02 16:22:46 · 2 answers · asked by Yorkie1961 2 in Science & Mathematics Mathematics

2 answers

The product rule says that the derivative of a product is the first factor times the derivative of the second, plus the second factor times the derivative of the first.

If we let u = cos(x) and v = e^(-xsqrt(3)) then

f'(x) = uv' + u'v

u' = -sin(x)

You will need to use the chain rule to get v'. Remember that the derivative of e^x is e^x.

2007-01-02 16:28:26 · answer #1 · answered by ? 6 · 0 0

product rule :f,u,v functions

f = u.v
f' = u'v + uv'

for you u = cosx, v=e^xsqrt(3)
u'=-sinx, v' = sqrt(3)e^xsqrt(3)

have fun

2007-01-03 00:29:00 · answer #2 · answered by gjmb1960 7 · 0 0

fedest.com, questions and answers